2011
DOI: 10.1007/s12350-010-9302-7
|View full text |Cite
|
Sign up to set email alerts
|

Tetrofosmin early time gated post-stress single-photon emission computed tomography imaging: Feasibility and potential benefits

Abstract: BackgroundThe purpose of this study is to evaluate the feasibility, the image quality, and the clinical relevance of an early gated post-stress (GPS) single-photon emission computed tomography (SPECT) tetrofosmin (Myoview™—GE Healthcare) acquisition protocol. Time delay between myocardial technetium-labeled tracer administration and SPECT acquisition is usually about 30 minutes after stress, and 45 to 60 minutes at rest: because of the absence of significant redistribution, perfusion images are related to stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
4
6
0
1
Order By: Relevance
“…These findings are in agreement with the EF values in negative patients as recently reported by Philippe et al [16]. Patients with negative perfusion scintigraphy constituted the control group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with the EF values in negative patients as recently reported by Philippe et al [16]. Patients with negative perfusion scintigraphy constituted the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The long-term prognostic value of poststress EF in addition to SDS or SSS in predicting adverse cardiac events, myocardial infarction, or cardiac death has already been shown in previous studies [9][10][11][12][13][14][15][16][17][18][19]22]; however, our report emphasizes the importance of early postexercise EF evaluation for referring patients for coronary angiography and revascularization. Resting EF does not reflect poststress stunning, and the prognostic value of poststress EF may be attributed to the transient worsening of ventricular function in patients with stressinduced ischemia and extensive coronary disease.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The latter difference was largely limited to patients undergoing adenosine stress, an observation compatible with the classic knowledge that stress with vasodilators is associated with a higher risk of subdiaphragmatic 99m Tc activity compared to exercise. Hence, our findings support the feasibility of early imaging and are in agreement with more recent, non-controlled 19,20 and controlled 8,21 studies, which have also demonstrated the feasibility of early imaging in terms of image quality appropriate for reliable interpretation. Furthermore, in our study the Early imaging protocol had similar diagnostic accuracy with the Late imaging protocol, demonstrating that early imaging is both technically feasible and diagnostically sufficient compared with the established imaging protocol.…”
Section: Discussionsupporting
confidence: 92%
“…They confirmed results from previous studies evaluating the same issues. [16][17][18] A fast MPI protocol including both rest and stress studies has several clinical implications. On the practical side, it offers a shorter waiting times and convenience to the patient and it increases the laboratories efficiency, possibly doing more studies per day.…”
mentioning
confidence: 99%